2002
DOI: 10.1274/jmor.19.1
|View full text |Cite
|
Sign up to set email alerts
|

Serious Limitation of Preimplantation Genetic Diagnosis

Abstract: Preimplantation genetic diagnosis (PGD) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We reported PGD by means of two-step FISH for chromosome-X, Y, 13, 16, 18, 21 and 22 [16]. Gianaroli et al [17] reported that screening for chromosome-X, Y, 13,14,15,16,18, 21 and 22 has an immediate impact on implantation rate.…”
Section: Means Of Overcoming Disadvantages (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…We reported PGD by means of two-step FISH for chromosome-X, Y, 13, 16, 18, 21 and 22 [16]. Gianaroli et al [17] reported that screening for chromosome-X, Y, 13,14,15,16,18, 21 and 22 has an immediate impact on implantation rate.…”
Section: Means Of Overcoming Disadvantages (2)mentioning
confidence: 99%
“…Two days are made available for diagnosis. The sufficient time for diagnosis makes it possible to attempt to obtain information on all chromosomes, such as visualization of metaphase plates or in vitro culture of single biopsied blastomeres [18]. Although PGD to screen chromosomal abnormalities on embryos is invasive and is not permitted in Japan, the combination of PGD and BT will make it possible to transfer blastocysts without chromosomal abnormalities.…”
Section: Means Of Overcoming Disadvantages (2)mentioning
confidence: 99%